Evaluation of rosmarinic acid against myocardial infarction in maternally separated rats - Verma H.; Bhattacharjee A.; Shivavedi N.; Nayak P.K. (My University, 2025)
Depression and coronary heart diseases are the common comorbid disorder affecting humans globally. The present study evaluated the effectiveness of rosmarinic acid (RA) against myocardial infarction (MI) in comorbid depression induced by maternal separation in rats. Maternal stress is one of the childhood crises that may be a potential risk factor for coronary heart disease in later part of life. As per protocol, 70–80% of pups were separated daily for 3 h between postnatal day 1 (PND1) and postnatal day 21 (PND21). Forced-swim test, sucrose preference test, and electrocardiography were performed during the experiment. Body weight was measured on PND0, PND35, and PND55. Orally rosmarinic acid (25 mg/kg and 50 mg/kg) and fluoxetine (10 mg/kg) was done from PND35 to PND55. On PND53 and PND54, isoproterenol (100 mg/kg, subcutaneously) was administered to induce myocardial infarction. On PND55, blood was collected and animals sacrificed, and plasma corticosterone, brain-derived neurotrophic factor, cardiac biomarkers, interleukine-10, and anti-oxidant parameters were measured. Rosmarinic acid and fluoxetine ameliorated the maternal separation–induced increase in immobility period, anhedonia, body weight, ST elevation, corticosterone, creatine kinase-MB (CK-MB), and lactate dehydrogenase (LDH). At the same time, both drugs elevated the tissue levels of BDNF, IL-10, glutathione, and superoxide dismutase activity. This study provides the first experimental evidence that maternal stress is an independent risk factor of cardiac abnormalities in rats. Moreover, maternal stress synergistically increases the severity of cardiac abnormalities induced by isoproterenol. Interestingly, fluoxetine and rosmarinic acid effectively ameliorated behavioral anomalies and myocardial infarction in maternally separated rats. Graphical abstract : Schematic representation of possible molecular mechanism of action of rosmarinic acid against MS-induced myocardial infarction. RA, rosmarinic acid; MS, maternal separation; PND, postnatal days; ISO, isoproterenol; BDNF, brain-derived neurotrophic factor; GSH, glutathione; SOD, superoxide dismutase; IL-10, interleukin-10; MI, myocardial infarction [Figure not available: see fulltext.] © 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.